Clinicopathologic Profiles of Sporadic Late-Onset Nemaline Myopathy: Practical Importance of Anti–α-Actinin Immunostaining. Issue 4 (17th July 2022) - Zhao, Bing; Dai, Tingjun; Zhao, Dandan; Ma, Xiaotian; Zhao, Cuiping; Li, Ling; Sun, Yuan; Zhang, Yongqing; Yan, Yaping; Lu, Jian-Qiang; Liu, Fuchen; Yan, Chuanzhu
Abstract : Background and Objectives: Sporadic late-onset nemaline myopathy (SLONM) is a treatable or otherwise fatal myopathy. Diagnosis of SLONM is still challenging, and no therapeutic consensus has been achieved. Here, we reported the clinicopathologic features and long-term follow-up data of SLONM in a Chinese cohort. Methods: We performed a retrospective evaluation of clinical, pathologic, and treatment outcomes of 17 patients with SLONM diagnosed between March 1986 and April 2021 at our neuromuscular center. Immunohistochemistry (IHC) with antibodies against 5 Z-disc–associated proteins was performed in the muscle biopsies of SLONM to identify a potential pathologic marker in aid of diagnosis. In comparison, we also performed muscle IHC in patients with selective type II fiber atrophy (n = 22), neurogenic atrophy (n = 22), mitochondrial myopathy (n = 5), immune-mediated necrotizing myopathy (n = 5), and normal controls (n = 5). Results: Most of the patients exhibited asymmetric limb muscles weakness (71%, 12/17) and neck extensor weakness (53%, 9/17). Immunofixation electrophoresis was performed in 11 patients, and 4 of them were identified with monoclonal gammopathy of undetermined significance (MGUS). EMG from 16 patients demonstrated a myopathic pattern with spontaneous activities in 69% (11/16) of them. Muscle MRI showed preferential involvement of paraspinal, gluteus minimus and medius, semimembranosus, and soleus muscles. Suspected nemaline bodies on modified Gomori trichrome were confirmed by IHC using anti–α-actinin antibody (100%, 17/17), anti-myotilin antibody (94%, 16/17), anti-desmin antibody (94%, 16/17), anti–α-B crystallin antibody (65%, 11/17), and anti-telethonin antibody (18%, 3/17) with various positive rates. Notably, anti–α-actinin IHC showed the highest percentage of strongly positive staining (77%, 13/17), being the only one without negative results. Moderate improvement following autologous stem cell transplantation (ASCT) was noted in 3/4 patients with MGUS; favorable outcomes were also achieved in 6/7 patients without MGUS, including 3 patients with complete recovery who were given a combined treatment of prednisone and another immunosuppressant. Discussion: SLONM is a treatable myopathy with ASCT or traditional immunotherapy, especially when combined with steroids and immunosuppressants. Anti–α-actinin immunostaining is the most reliable pathologic marker to identify rod-bearing fibers, and it should be performed routinely in adult patients with undiagnosed nonnecrotic myopathies.